THE PSCHONEUROLINGUISTIC SITUATION AND THE PLACE OF CANONICAL PROPOSAL MODELS IN TEACHING A FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2023)
Present article analyses a role of the modern neurolinguistics  and methodics of teaching French language, due to the forming of communicative skills, which plays a huge part at studying process. The main directions of the neurolinguistic researches, their importance in linguistics is shown.